2019
DOI: 10.2196/12658
|View full text |Cite
|
Sign up to set email alerts
|

Use, Perspectives, and Attitudes Regarding Diabetes Management Mobile Apps Among Diabetes Patients and Diabetologists in China: National Web-Based Survey

Abstract: Background The diabetes disease burden in China is heavy, and mobile apps have a great potential for diabetes management. However, there is a lack of investigation of diabetes app use among Chinese diabetes patients and diabetologists. The perspectives and attitudes of diabetes patients and diabetologists regarding diabetes apps are also unclear. Objective Our objectives were to investigate diabetes patients’ and diabetologists’ use, attitudes, and perspectives, as well… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 45 publications
(63 reference statements)
6
88
0
4
Order By: Relevance
“…In our study 42.3% of the respondents aged between 21 and 30 years old, which is the dominant age range. The predominant age range in similar studies were: 30-39 (34%) [16], 26-35(44%) in [15], 25-34 (51.7%) in [17], 30-39 (45.1%) in [22] and 50-59 (32%) in [14], while Sauceda et al [18] did not report the age of participants. Therefore, most similar studies have a similar or slightly older predominant age range than our study, while in Karduck et al The respondents were even older [14].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In our study 42.3% of the respondents aged between 21 and 30 years old, which is the dominant age range. The predominant age range in similar studies were: 30-39 (34%) [16], 26-35(44%) in [15], 25-34 (51.7%) in [17], 30-39 (45.1%) in [22] and 50-59 (32%) in [14], while Sauceda et al [18] did not report the age of participants. Therefore, most similar studies have a similar or slightly older predominant age range than our study, while in Karduck et al The respondents were even older [14].…”
Section: Discussionmentioning
confidence: 84%
“…In similar studies where only dietitians were included, the respective percentage was 95% [15], 98.3% [17] and 96.1% in [14]. In Zhang et al [22] the participants were diabetes specialists and the respective percentage was 67.6%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The superficial exploration is likely reinforced by the large availability of different apps in the diabetes field. Furthermore, the use may be impacted by the price of the app (the app used in this study is free of charge), and if the app is selected in collaboration with an HCP [ 27 , 28 ]. A survey among patients with diabetes in China revealed that only 19% of the apps were recommended by HCPs, whereas most users selected their app randomly or as recommended by other patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying reason is that the apps were designed without the participation of medical professionals. Without incorporating recommendations from physicians on diagnosis or treatment, the apps lack the high-quality proof of effectiveness that can be obtained from clinical trials (23).…”
Section: Current State Of Diabetes Education/management and Existing mentioning
confidence: 99%